If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(7*x+7/8)*(7*x-(1/7)) = 0
(7*x+7/8)*(7*x-1/7) = 0
( 7*x+7/8 )
7*x+7/8 = 0 // - 7/8
7*x = -7/8 // : 7
x = -7/8/7
x = -1/8
( 7*x-1/7 )
7*x-1/7 = 0 // + 1/7
7*x = 1/7 // : 7
x = 1/7/7
x = 1/49
x in { -1/8, 1/49 }
| 5(-12-32)/9= | | -9+3+2(a)=-2 | | -5x-7=-4x-8 | | 7x+5=-11x-13 | | 3x=6x-12 | | 8-4a=-8 | | -7x-5=-3x-13 | | -5x+5=3x-11 | | 12x+5=8x-7 | | x^5/8*x^3/8 | | 3a+4=7a-12 | | -12x+5=3x-10 | | -16=-2c | | -6=-2c | | 1/3-a=2 | | (2x-5)(x+5)=0 | | (2x+5)(x-5)=0 | | (2x+1)(x-25)=0 | | (6x+27)(9x+1)=0 | | -6a=a+2 | | (6x+1)(9x+27)=0 | | (6x+9)(9x+3)=0 | | 7x+4y/3(9x) | | (6x+3)(9x+9)=0 | | 7x/3+4y/9x | | (6x+7)(9x+5)=0 | | 14.5x= | | =14.5x | | t-2=13 | | (6x+5)(9x+7)=0 | | y=14.5 | | p=2(27)+2(34) |